Maximizing the Impact of Control at All Levels - Visioli, Antonio (Frontiers in Control Engineering, 2020)
The paper discusses the strategies that should be applied to maximize the impact of control systems in our society. This is achieved, in particular, by revealing the role of control systems (at different levels) in different fields and by reducing the theory/practice gap so that methodologies proposed by academic researchers can be transferred to industry. Some considerations about the role of scientific publications are also made.